Status of construction and first tests of the CLEO III RICH - Artuso, M; Azfar, F; Efimov, A; Kopp, S; Mountain, R; Schuh, S; Skwarnicki, T; Stone, S; Viehhauser, G; Anderson, S; Smith, A; Kubota, Y; et al. (IEEE, 1998)
The CLEO collaboration is preparing a major upgrade of its present detector including a RICH detector for particle identification. This subdetector system follows the 'proximity focussing' design and uses Lithium Fluoride (LiF) crystal radiators and MWPCs as photon detectors. These chambers are filled with a CH4/TEA gas mixture and have a Calcium Fluoride (CaF2) crystal photon entrance window. Part of the radiator crystals will have the new 'sawtooth' geometry.We have constructed two of the 30 detector modules and tested these together with the first planar and 'sawtooth' radiator crystals in a muon halo beam at Fermilab. For the measurement of the Cherenkov angle we obtain a single photon measurement error of 13.5 mrad for the conventional planar radiator. With 14 detected photons we find a resolution per track of 4.5 mrad. In the first measurement ever of a 'sawtooth' radiator we achieve a resolution of 11.8 mrad for single photons and 4.8 mrad per track for 12.3 detected photons With a reduced geometric acceptance. These results fulfill CLEO III requirements.